Integrasi Kearifan Lokal dalam Materi IPS untuk Menumbuhkan Rasa Cinta Tanah Air pada Siswa SD Negeri 3 Kuala - Raziska Ibrahimi; Tria Marvida (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Instilling national values from an early age is crucial for shaping the character of a young generation who love their homeland. One strategic effort is to integrate local wisdom into Social Studies (IPS) learning in elementary schools. This study aims to describe the integration of local wisdom into the IPS curriculum and its impact on fostering patriotism among students at Kuala 3 Public Elementary School. This research used a descriptive qualitative approach using observation, interviews, and documentation techniques. The results indicate that introducing local values such as customs, folklore, traditional ceremonies, and local figures in IPS lessons can foster a sense of pride and belonging in one's own cultural identity. Teachers play a central role in designing learning materials that are contextual and relevant to the surrounding environment. Furthermore, student involvement in local culture-based learning activities such as role-playing, making traditional crafts, and listening to local stories increases their participation and motivation to learn. Thus, integrating local wisdom into IPS learning not only enriches the teaching material but is also effective in fostering nationalism from an early age.